Student Motivation Using Virtual Reality in Human Anatomy and Physiology Courses - Thadani, Avinash; Deschamps, Isabelle; Doran, James; Forlani, Cassandra; Theriault, Rob; Madorin, Sean (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2025)
This study investigates student motivation using virtual reality (VR) technologies in anatomy and physiology courses. Over a two-year period, 21 college students from nursing, paramedic, and biotechnology-health programs were recruited for this study. The participants were randomly assigned to either a group using immersive VR on Quest 2 headsets or a group using desktop-based VR on personal computers. Both groups utilized VR on the health education platform 3D-Organon. The study compares the intrinsic motivation between these two groups. Four subscales of the Intrinsic Motivation Inventory were employed for this study. The immersive VR group was statistically significantly higher on the interest/enjoyment and perceived competence subscales. There was no significant difference between the two groups on the pressure/tension and perceived choice subscales. This study demonstrates VR's potential in boosting student motivation in human anatomy and physiology courses. Due to limited participation in pre- and post-assessment tools, content-based learning gains could not be compared. This highlights challenges in conducting VR studies in postsecondary institutions, including volunteer bias, curriculum integration barriers, student recruitment, and survey fatigue. These insights are critical for administrators and pedagogical designers when evaluating wider VR adoption in health and science education.